Izglagolske izpeljanke s pomenom vršilca dejanja (Slavistična revija, 1992)
Derivatives with the meaning of the agent of an action are formed with a number of native and borrowed suffixes; among the most productive are -ač, -lec, -(a)tor, -ar, -er, -(a)nt, -ec and -telj. The same verbal base can be combined with various derivational morphemes typical for the group, however, these derivatives are not (or are very rarely) stylistically equivalent. Derivatives may carry one or two stresses, which are predictable on the basis of the prosodic characteristics of the bases and the formants.
Keywords: jezikoslovje; linguistics; Slovene; slovenščina